2019
DOI: 10.1007/s12519-019-00322-7
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risk factors for pulmonary hemorrhage in extremely low-birth-weight infants

Abstract: Background Pulmonary hemorrhage (PH) is a life-threatening respiratory complication of extremely low-birth-weight infants (ELBWIs). However, the risk factors for PH are controversial. Therefore, the purpose of this study was to analyze the perinatal risk factors and short-term outcomes of PH in ELBWIs. Methods This was a retrospective cohort study of live born infants who had birth weights that were less than 1000 g, lived for at least 12 hours, and did not have major congenital anomalies. A logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…PH can start gradually and continue for a long time, or it can be a sudden life-threatening respiratory complication associated with several risk factors ( 12 ). We identified multiple risk factors to be independently associated with pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PH can start gradually and continue for a long time, or it can be a sudden life-threatening respiratory complication associated with several risk factors ( 12 ). We identified multiple risk factors to be independently associated with pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…These preterm babies that experienced PH were critically ill with clinical conditions like sepsis or neonatal encephalopathy. It has been shown that small for gestational age, early onset neonatal sepsis, low birth weight, lower Apgar scores at 1 and 5 min, severe RDS, and surfactant replacement were all risk factors for PH ( 12 ). Another study from a neonatal intensive care unit in Brazil reported prior use of blood components to be an independent risk factor for PH ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 251 studies were retrieved; after removing duplicates, initial screening and reading the full texts, a total of 13 studies were included [17][18][19][20][21][22][23][24][25][26][27][28][29] . The literature screening process is shown in Figure 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Asphyxia, prematurity, intrauterine growth restriction, infection, hypoxia, and patent ductus arteriosus (PDA) have been considered as perinatal risk factors for pulmonary hemorrhage by different researchers [ 7 , 8 , 9 ]. Moreover, pulmonary hemorrhage has also been reported related to tracheal intubation in the delivery room [ 10 ].…”
Section: Introductionmentioning
confidence: 99%